Supramolecular Polymerization of all-cis-Fluorinated Cyclohexanes: Influence of Side Chains - Haridas, Shyamkumar V.; Shyshov, Oleksandr; von Delius, Max (Organic Materials, 2023)
Custom-designed materials based on supramolecular polymers are of interest for applications in organic electronics and biomedicine. Recently, we have shown that derivatives of the highly polar compound all-cis hexafluorocyclohexane undergo seeded polymerization and can therefore be used to prepare soluble nanofibers with controlled length. In this work, we aimed to explore the scope of this process. We studied the supramolecular polymerization of six all-cis-fluorinated cyclohexane monomers, with five differing in the solubilizing side chains and one in the secondary supramolecular binding site. In studies on controlled supramolecular polymerization, we found that three of the monomers could be induced to polymerize by ultrasound irradiation and four by addition of seeds. For these latter examples, we were able to identify a solvent mixture that led to spontaneous polymerization and hysteresis in heating and cooling curves. These results show that the living supramolecular polymerization of fluorinated cyclohexanes is not limited to one particular monomer, but that side chains exhibiting a strong solvophobic effect that cannot be compensated within the binary solvent “window” represent a limitation to the approach. We also demonstrate that nanofibers based on stacks of fluorinated cyclohexanes can be dissociated by addition of chloride ions.
Keywords: supramolecular polymers; seeded polymerization; C–H hydrogen bonds; CD spectroscopy